Impacts of crumb rubber surface treatments on the strength of rubberised mortar - Aminuddin, Alia Nazifa; Wan Hassan, Wan Nur Firdaus; Saad, Siti Asmahani; Md. Husain, Nadiah; Che Deraman, Siti Noratikah (Springer, 2025)
Ever since the first production in 6500 BC, the amount of concrete has been increasing over the years. Though it is one of the viable construction elements, its high consumption of natural resources can lead to resource scarcity, which urgently directs the exploration of the potential alternatives in shifting the concrete to become a more environmentally friendly material. Considering that waste tyre rubber can function as aggregate, the idea of rubber-incorporated concrete seems attractive. However, previous research reported that the mechanical properties of concrete are negatively affected by the poor interaction of rubber particles in the cement matrix. To counteract this issue, various rubber treatment methods, which include mechanical, chemical, thermal, and microwave treatment, have been designed as the groundwork of other scientists to enhance the rubberised concrete properties. This paper focuses on characterising the early strength of rubber-treated cement mortars under three reliable methods: thermal, immersion in alkali solution, and oxidation-sulfonation process. Another aim of this study is to find the best treatment method for modifying crumb rubber (CR) that is feasible enough to be implemented in the industry from technical, practical, and economical point of view. In achieving the objectives, several testing methods are done to obtain the required data for the anal-ysis: vicat testing, sieve analysis and compressive testing. The results show that thermal treatment is the most favourable treatment because the incorporated rubber mortar can match the strength of the controlled mortar. The mortar samples incorpo-rating thermally treated rubber demonstrated the lowest percentage of compressive strength loss (18%) compared to untreated rubber (44%), rubber treated using alkali immersion (35%) and oxidation-sulfonation (52%). Scanning Electron Microscopy (SEM) images were also presented in this paper, which are necessary in explaining the reasons behind the mortar compressive strength data. Thermally treated rubber exhibited smoother surfaces with reduced porosity, contributing to improved bonding and reduced water penetration in the cement matrix. Though this study highlights the potential of using rubber crumbs as a sustainable alternative to sand in mortar, addressing environmental concerns and promoting circular economy principles, future studies should explore the environmental quality assessment of rubberised concrete and mortar, as well as investigate optimal rubber crumb sizing for improved compatibility with conventional aggregates.